Pengembangan Bahan Ajar Kimia Inovatif pada Pokok Bahasan Reduksi dan Oksidasi Berdasarkan Kurikulum 2013 Terintegrasi Pendidikan Karakter - Elisabet Singarimbun; Ramlan Silaban; Retno Dwi Suyatni; Iis Siti Jahro; Manihar Situmorang (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. This study aims to determine: (1) whether the chemical innovative teaching materials developed for SMA / MA class X second semester on the subject of the oxidation reduction was decent and in accordance with the curriculum, 2013. (2) Does the use of innovative teaching materials chemistry development results provide results better learning for SMA / MA class X second smester with the students taught without the use of chemicals innovative teaching materials that have been developed based on the curriculum of 2013. (3) Does the use of innovative teaching materials chemistry results can foster the development of a better character to students SMA / MA X class second semester than students taught without the use of chemicals innovative teaching materials that have been developed based on the curriculum of 2013. This study uses qualitative data described through a questionnaire with eligibility sheet book contains indicators of assessment from the National Standards Body .Education (BSNP) and quantitative data to determine the effectiveness of the use of the results of Instructional Materials for learning outcomes and student character. The study population was all students in the second semester of class X SMA Negeri 1 Salapian, SMA 1 and SMA Kuala 1 Bahorok. The treatment sample of 2 classes of experimental class I and class II experiment at each school. Data collected by an objective test for student learning outcomes before and after the learning process, a questionnaire to measure the character sheet. Data were analyzed using SPSS 17.0 with a significance level of 0.05. The results of the assessment form validation mean to determine the feasibility of innovative teaching materials Oxidation Reduction. The results were obtained: (1) innovative teaching materials developed for the oxidation reduction SMA / MA class XI second semester  was decent and in accordance with the curriculum in 2013 based on the results of the feasibility of standardizing the contents of 3.63, standardize language feasibility3.64, feasibility standardize the presentation of 3,66, standardization grafic of 3.67 (2) There are significant differences chemistry student learning outcomes SMA / MA Class X second semester is taught with the use of innovative teaching materials on the subject of chemical oxidation reduction that has been developed based on the curriculum in 2013 is higher than the student learning outcomes are taught without the use of innovative teaching materials on the subject of chemical oxidation reduction that has been developed based on the curriculum of 2013. (Sig.1-tailed <α (0.000 <0.05)) (3) There are significant differences of character development of students SMA / MA Class X second semester is taught with the use of innovative teaching materials on the subject of chemical oxidation reduction that has been developed based on the curriculum in 2013 is higher than the character development of students who are taught by without the use of innovative teaching materials on the subject of chemical oxidation reduction that has been developed based curriculum in 2013. Keywords: teaching material reduction of oxidation, front page, learning outcomes, communicative, responsibility jawab. kreativity